Giant bicycle : bike-sharing in taipei - Springer, Nikki; Dana, Jason (London : Yale School of Management, 2022)
This case tells the story of Giant Bicycle, a bicycle manufacturer based in Taiwan, who is trying to increase the popularity of the bike share scheme YouBike. YouBike has lost over ten million dollars to date and has seen very ridership with only 23 bike rides a day. Giant Bicycle must now decide if it wants to continue supporting the bike share scheme since the business model is only tangentially related to its core business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Urban transportation -- Case studies; Strategic planning; Decision making